Odpowiedzi

  • Użytkownik Zadane
2010-01-11T17:21:10+01:00
A) 1+(6a + 4) - 2a= 1+6a + 4 -2a=1+4+6a-2a+4=5+4a
b) (7,5x - 3y - 6) +3y=7,5 -3y -6 +3y=7,5x-3y+3y- 6=7,5x+y
c) 2xy + (x kw - 5xy)=2xy +x² - 5xy=2xy - 5xy+x² =-3xyx²
d) 7a + (-4a - 11) + 6,3=7a + (-4a) - 11 + 6,3=7a-4a- 11 + 6,3=3a+4,7
e) 5a kw + (6-4a kw)=5a²+ 6-4a²=5a²-4a²+6=a²+6
f) (5c - 4) + (11 - 8c)=5c - 4 + 11 - 8c=5c-8c- 4 + 11=-3c+7
2 3 2
2010-01-11T17:22:00+01:00
A) 1+(6a + 4) - 2a= 1+ 6a+4-2a= 4a+5
b) (7,5x - 3y - 6) +3y= 7,5x-3y-6+3y= 7,5x-6
c) 2xy + (x kw - 5xy)=2xy+ x kw -5xy= x kw-3xy
d) 7a + (-4a - 11) + 6,3= 7a-4a-11+6,3=3a-4,7
e) 5a kw + (6-4a kw)= 5a kw +6-4a kw= a kw+6
f) (5c - 4) + (11 - 8c)= 5c-4+11-8c= -3c+7
4 3 4